ANALYSIS OF WORK DISCIPLINE OF CIVIL SERVANTS IN THE REGIONAL CIVIL SERVICE AGENCY OF CENTRAL JAVA PROVINCE - Abyan Iqra Pradana; Ida Hayu Dwimawanti (Journal of Public Policy and Management Review, 2019)
This study aims to analyze work discipline and inhibiting factors and drivers of work discipline of civil servants in the Regional Civil Service Agency of Central Java Province. Based on the results of the study indicate that the work discipline of civil servants in the Regional Employment Agency of Central Java Province has not been good. This is seen from the presence of employees who are not on time and do not comply with the rules at work. Employee discipline is inseparable from supporting and inhibiting factors. Supporting and inhibiting factors can be seen in terms of leadership and aspects of motivation. The leadership factor in terms of leadership is the absence of strict sanctions regarding disciplinary violations. The inhibiting factor in terms of motivation is the absence of motivation for employees. Based on the obstacles that exist in achieving employee work discipline in the Central Java Regional Personnel Agency, the author provides recommendations in the form of: (1) Leaders to provide more motivation and attention to the discipline of their employees. (2) Leaders make a list of staff work needs to support work which is then seen as useful. (3) The application of rewards to subordinates at least once a year. (4) Enforcement of strict sanctions regarding discipline specifically for employees of the Regional Civil Service Agency of Central Java Province.